(untitled) (Hematology Meeting Reports, 2009)
The presence of antiphospholipid antibodies is linked to an increased rate of repeated spontaneous abortions and fetal deaths, that in fact belong to the clinical spectrum of the antiphospholipid syndrome. The pathogenic role of antiphospholipid antibodies was clearly shown in experimental animals that, when infused during pregnancy, develop placental insufficiency and miscarriages. In addition, in vitro aPL were shown to bind trophoblastic cells and to impair their function. However, since pregnant patients with this condition were appropriately managed, APS was defined as one of the few tractable cause of pregnancy losses. In fact, despite a significant number of complications still recorded, the large majority of these pregnancies now end with life births. Data on perinatal and long-term outcome of children born to patients with antiphospholipid antibodies are reassuring.